1992
DOI: 10.1177/002203459207100s27
|View full text |Cite
|
Sign up to set email alerts
|

Demineralization and Remineralization Evaluation Techniques

Abstract: This paper compares the experimental techniques utilized to assess the de- or remineralization of enamel or dentin in intra-oral studies. In in situ studies, it is important for one to know how much mineral has been lost or gained, and where the loss or gain occurred. The main emphasis in this paper is on techniques suitable for direct or indirect mineral quantification. The measuring techniques considered are microradiography, iodine absorptiometry, various microhardness tests, polarized light, light-scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
209
1
30

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(241 citation statements)
references
References 22 publications
1
209
1
30
Order By: Relevance
“…The use of SH loss to evaluate enamel-dentin demineralization is supported by the available literature. 8,20 Although our results contradict those found by ten Cate et al, 1 these authors used an in vitro design, which may account for the observed differences compared to our in situ study.…”
Section: Discussioncontrasting
confidence: 98%
“…The use of SH loss to evaluate enamel-dentin demineralization is supported by the available literature. 8,20 Although our results contradict those found by ten Cate et al, 1 these authors used an in vitro design, which may account for the observed differences compared to our in situ study.…”
Section: Discussioncontrasting
confidence: 98%
“…It has been reported that the accuracy of TMR for enamel was approximately 5 m for Ld and approximately 200 for Z (Vol m), regardless of the digitalizing method 4) . In light of this finding 4) , the TMR procedure was employed in the present study. To calculate the mineral content profile, TMR films were scanned.…”
Section: Discussionmentioning
confidence: 99%
“…According to a review by Arends and Bosch, TMR is the most widely used technique to evaluate tooth mineralization, despite some inherent disadvantages 4) . It has been reported that the accuracy of TMR for enamel was approximately 5 m for Ld and approximately 200 for Z (Vol m), regardless of the digitalizing method 4) . In light of this finding 4) , the TMR procedure was employed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reviews have been published on the wide array of methods that have been developed to quantify changes in mineral status of tooth specimens . 33,34,36 The UK group identified those methods that have received general acceptance by the research community. These included the following qualitative methods: Of the methods currently validated, TMR was considered to be the most informative, but is also the most demanding.…”
Section: Methods Of Measurementmentioning
confidence: 99%